Pemberdayaan Pemimpin Desa dalam Mendorong UMKM dan Ekonomi Kreatif Lokal Berbasis Desa Wisata - Bahasoan, Husen; Wargadinata, Betty; Ansari, Ansari; Fauziansyah, Fauziansyah (Penerbit Widina, Widina Media Utama, 2025)
This article is the result of a community service activity was conducted by the Young Generation of the Lecturer Communication Forum (GM FKD) on March 20, 2025, in West Bandung Regency. Its objective was to empower village leaders in promoting the growth of MSMEs and the creative economy based on local potential. With its significant tourism potential, the village has opportunities to develop culinary businesses, handicrafts, and tourism services. However, challenges such as limited capital and lack of marketing knowledge remain obstacles. This activity included seminars, education, and interactive discussions attended by 30 village officials. The materials covered business strategies, digital marketing, and safe access to financing. As a result, village leaders gained a better understanding of their role in developing MSMEs and the importance of innovation in marketing. With support from various stakeholders, the village has the potential to become a creative economy hub based on tourism. This initiative is expected to improve community welfare and serve as a model for sustainable MSME development.ABSTRAKArtikel ini merupakan hasil kegiatan pengabdian kepada masyarakat ini dilakukan oleh Generasi Muda Forum Komunikasi Dosen (GM FKD) pada 20 Maret 2025 di Kabupaten Bandung Barat. Tujuannya adalah memberdayakan pemimpin desa dalam mendorong pertumbuhan UMKM dan ekonomi kreatif berbasis potensi lokal. Dengan potensi wisata yang besar, desa ini memiliki peluang untuk mengembangkan usaha kuliner, kerajinan, dan jasa wisata. Namun, tantangan seperti keterbatasan modal dan kurangnya pemahaman pemasaran masih menjadi kendala. Kegiatan ini meliputi seminar, edukasi, dan diskusi interaktif yang diikuti oleh 30 perangkat desa. Materi mencakup strategi bisnis, pemasaran digital, dan akses permodalan yang aman. Hasilnya, pemimpin desa semakin memahami peran mereka dalam mengembangkan UMKM serta pentingnya inovasi dalam pemasaran. Melalui dukungan berbagai pihak, desa ini berpotensi menjadi pusat ekonomi kreatif berbasis wisata. Kegiatan ini diharapkan dapat meningkatkan kesejahteraan masyarakat dan menjadi model pengembangan UMKM yang berkelanjutan.